Prevention Of Bullying Among Adolescents In The Lens Of Indonesian Policy And Law: Should Nurses Know? - Wuryaningsih, Emi Wuri; Wahyuni, Budi; Lusmilasari, Lely; Haryanti, Fitri (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2022)
Introduction: Indonesia has several institutions, policies, and laws to protect children from all forms of violence, including bullying that impacts physical, psychological, and social health and even death. However, the number of cases of bullying in adolescents still increases. It is related to a lack of knowledge about bullying and is associated with norms in the community. Method: The analysis uses a discourse analysis approach, "What's the problem represented to be". This method analyzes how the problem of bullying among adolescents is formed, and the forms of bullying prevention are represented in state documents. The analysis steps include: collecting the policy documents related to child protection and health (seven laws and three national policies); Reading the policy text as a whole; rereading the text and underlining the concepts; doing coding and theme analysis; and answering the question. Results: Three main problems of bullying in adolescents that can be identified include: Theme 1. Terminology of children and adolescents; Theme 2. Children are a vulnerable and disempowered group; Theme 3. Agreement and clarity on child protection related to violence, especially bullying, with perpetrators and victims being children. Conclusions: Laws and policies have a crucial role in constructing and representing the problem of adolescent bullying in Indonesia. Nurses can use these results to develop adolescent bullying prevention programs through firmness and alignment with policies and legislation.